Pengembangan Kurikulum Pendidikan Agama Islam Berbasis Outcome Based Education (OBE) di Perguruan Tinggi - Andi Fitriani Djollong; Zulbina Zulbina; Mardiati M; Karmila Karmila; Rosiana Syahbaniar; Rudi Hartono; Muh Iqbal Muhidin (Jurnal Pendidikan, Kepelatihan, Olahraga, dan Kesehatan, 2026)
The development of the Islamic Religious Education (PAI) curriculum in higher education continues to evolve in response to globalization, technological advancement, and the demand for 21st-century competencies. One widely adopted approach in curriculum development is Outcome-Based Education (OBE), which emphasizes graduate learning outcomes as the primary orientation of education. This study aims to examine the development of an OBE-based PAI curriculum in higher education through a systematic literature review approach. The research method employed a literature study by collecting relevant scientific sources, including journals, books, articles, and educational policy documents related to the implementation of OBE in higher education. A total of 21 literature sources were analyzed to ensure the transparency, validity, and rigor of the review process. Data were analyzed using descriptive qualitative techniques through data reduction, classification, and interpretation stages. The findings indicate that the implementation of OBE in the PAI curriculum contributes to improving learning quality by emphasizing students’ spiritual, academic, social, and professional competencies. Furthermore, OBE promotes student-centered learning and strengthens outcome-based assessment practices. However, the implementation of the OBE-based PAI curriculum still encounters several challenges, such as limited lecturer understanding, insufficient training, and difficulties in developing authentic assessment instruments. Therefore, institutional policy strengthening, lecturer capacity building, and the development of a systematic evaluation framework are required to ensure the effective and sustainable implementation of OBE in Islamic Religious Education (PAI) curriculum in higher education institutions. This study is expected to provide theoretical contributions and practical implications for curriculum development in Islamic higher education institutions practice.